Structural properties of zinc oxide thin films deposited on various substrates - C.G., Ching; P.K., Ooi; S.S., Ng; Hassan, Z.; Abu Hassan, H.; Abdullah, M.J. (Universiti Kebangsaan Malaysia, 2014)
In this work, the structural properties of radio frequency sputtering-grown zinc oxide (ZnO) thin films on sapphire (Al2O3), gallium arsenide (GaAs) and n-type silicon (Si) substrates were characterized. Scanning electron microscopy was employed to study the surface morphology of the samples. X-ray diffraction (XRD) measurements were also performed to obtain the structural information of the samples. The XRD results showed that the ZnO layers grown on different substrates have similar lattice constant (c) values, which were used to calculate the strain percentages of the ZnO thin films. The surface morphologies of the ZnO thin films indicated the formation of a granular surface when ZnO is deposited on n-type Si(100) and Si(111) substrates. Meanwhile, a leaf-like surface is obtained when ZnO is deposited on GaAs and Al2O3 substrates. The results showed that the ZnO thin film grown on n-type Si(100) has the best quality among all the samples.